2021
DOI: 10.1002/dvdy.386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide is necessary during tail regeneration in juvenile axolotl

Abstract: Background Hydrogen peroxide (H2O2) is a key reactive oxygen species (ROS) generated during appendage regeneration among vertebrates. However, its role during tail regeneration in axolotl as redox signaling molecule is unclear. Results Treatment with exogenous H2O2 rescues inhibitory effects of apocynin‐induced growth suppression in tail blastema cells leading to cell proliferation. H2O2 also promotes recruitment of immune cells, regulate the activation of AKT kinase and Agr2 expression during blastema formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 96 publications
(261 reference statements)
7
31
0
Order By: Relevance
“…It was first demonstrated that during the very early phase of wound healing in the zebrafish larval tail fin, a Duox-dependent gradient of H2O2 is generated within 3 min at the wound margin, peaks at 20 min and is required for the recruitment of distant leukocytes 39 . Members of the NOX family were subsequently shown to be involved in regeneration per se, as is the case in the adult zebrafish caudal fin 13,22 and heart 14 , gecko tail 15 and juvenile axolotl or Xenopus tadpole tail 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…It was first demonstrated that during the very early phase of wound healing in the zebrafish larval tail fin, a Duox-dependent gradient of H2O2 is generated within 3 min at the wound margin, peaks at 20 min and is required for the recruitment of distant leukocytes 39 . Members of the NOX family were subsequently shown to be involved in regeneration per se, as is the case in the adult zebrafish caudal fin 13,22 and heart 14 , gecko tail 15 and juvenile axolotl or Xenopus tadpole tail 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…While excessive levels of ROS are detrimental to cellular homeostasis, previous studies show that at a certain threshold ROS act as important activators of signaling pathways. The translational control of ROS regulators is interesting as their activation at sites of injury is an important facet of regeneration in a variety of species, including zebrafish, frogs, planaria, and axolotls [27][28][29][30][31][32][33] . Selective translation of these proteins suggests that induction and a delicate balance of ROS during wound healing and regeneration is a part of a heretofore unexplored and tightly regulated post-transcriptional regulatory process.…”
Section: Polysome Sequencing Reveals Rapid 'On Demand' Remodeling Of Gene Expression At the Translation Level Upon Injurymentioning
confidence: 99%
“…Our polysome sequencing, detected translational activation of peroxiredoxin, an important antioxidant, within 24 hpa. Previous studies showed that sustained accumulation of ROS is critical for tissue regeneration [29][30][31]33 . In contrast, high levels are toxic, therefore cells must carefully orchestrate a balance of ROS production 51 .…”
Section: Mtor Is Required For Wound Healing and Regenerationmentioning
confidence: 99%
“…However, the time in which these stages occur differs from those of smaller animals with approximately 2-3 cm (Echeverri et al, 2001). Currently, in our laboratory, several ongoing projects are evaluating the effect of some signaling molecules involved in the regeneration of this structure such as reactive oxygen species (ROS) and their interaction with other signaling pathways, using chemical inhibitors that are placed directly on the aquatic environment (Carbonell et al, 2021). Given the location of the tail, its shape, and the relatively easy surgical access to the tissue, it allows tools such as electroporation of plasmids and other constructs to be quite viable (Echeverri and Tanaka, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%